2020
DOI: 10.3390/molecules25092244
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Characterization and Biological Activity Screening of Sodium Alginate-Gum Arabic Nanoparticles Loaded with Curcumin

Abstract: The approach of drug delivery systems emphasizes the use of nanoparticles as a vehicle, offering the optional property of delivering drugs as a single dose rather than in multiple doses. The current study aims to improve antioxidant and drug release properties of curcumin loaded gum Arabic-sodium alginate nanoparticles (Cur/ALG-GANPs). The Cur/ALG-GANPs were prepared using the ionotropic gelation technique and further subjected to physico-chemical characterization using attenuated total reflectance–Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 44 publications
0
25
0
2
Order By: Relevance
“…The absorbance was recorded using an ELISA reader at 570 nm. This colorimetric assay focused on the reduction of MTT to purple formazan by the mitochondrial enzymes of the metabolically active cancer cells 64 . The IC 50 was calculated from the concentration of drug that inhibits 50% of cell growth.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…The absorbance was recorded using an ELISA reader at 570 nm. This colorimetric assay focused on the reduction of MTT to purple formazan by the mitochondrial enzymes of the metabolically active cancer cells 64 . The IC 50 was calculated from the concentration of drug that inhibits 50% of cell growth.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Sodium alginate has been commonly used as an anionic polysaccharide due to its physicochemical, biocompatibility, and nontoxicity properties. Also, nanoparticle formulations containing alginate, which are known as bioactive agents, are suitable as a functional system in pharmaceutical properties [ 58 ]. Research has demonstrated that sodium alginate improved the selectivity of therapeutic agents release such as paclitaxel or doxorubicin in a certain area with enhancing safety.…”
Section: Methodsmentioning
confidence: 99%
“…Parenteral [194] Arabic gum Curcumin Parenteral [182] Hyaluronic acid-folic acid Oxaliplatin Oral [184] Artemisia ciniformis extract Paclitaxel Parenteral [181] Catechol Garcinia mangostana L. extract Parenteral [183] Gold nanoparticles Cisplatin Parenteral [195] Graphene oxide nanoplatelets Doxorubicin Parenteral [196] Iron oxide nanoparticles Doxorubicin Parenteral [198] Polyelectrolyte complexation Chitosan Doxorubicin Parenteral [186] Doxorubicin-paclitaxel Pulmonal [188] Cysteamine-disulphide-poly(allylamine hydrochloride) -poly(4-styrenesulfonic acid-co-maleic acid) sodium salt Paclitaxel Oral [191] Hair keratin Doxorubicin hydrochloride Parenteral [192] Chitosan-iron oxide nanoparticles Curcumin Parenteral [199] Gelation method/polyelectrolyte complexation…”
Section: Doxorubicinmentioning
confidence: 99%
“…NPs embedding curcumin were studied for their growth inhibition capacity and anticancer activity against liver, colon, lung, and breast cancer. [182] Also, catechol-functionalized alginate NPs loaded with Garcinia mangostana L. extract were explored in the treatment of bladder cancer. [183] Remarkably, the surface functionalization with catechol guaranteed both excellent mucoadhesive properties and could prolong residence on the mucous tissues compared with unmodified Alg-NPs, thereby increasing the drug therapeutic effect.…”
Section: Cancer Therapymentioning
confidence: 99%